Penguatan Literasi Bahasa Inggris Melalui Sosialisasi dan Pelatihan TOEFL bagi Mahasiswa Universitas Islam Makassar - Dahniar; Suhrah; Juspaningsih; Basri (Yayasan Habiburrahman Jamalu Bina Ummat, 2025)
This activity aims to improve the understanding and readiness of PGSD FKIPS students of the Universitas Islam Makassar for the TOEFL (Test of English as a Foreign Language) test, which has become a requirement and a need in the academic and professional world. Through socialization approaches, material training, TOEFL simulations, and reflection, participants are guided to understand the structure of the test, understand the types of questions, and practice answering strategies effectively. This activity was attended by around 80 students, and was held for three days at the Language Center of Universitas Islam Makassar. The results of the activity showed an increase in participants' knowledge of the TOEFL format and an increase in confidence in answering the test. Although there are still challenges in the aspects of listening, structure, and reading, participants showed progress in understanding the pattern of questions and answering strategies. This training is considered useful and relevant, and it is recommended to be held periodically as part of efforts to strengthen students' English language competencies in the university environment.